SIRT1: potential target in glucocorticoid-resistant diseases - Xie, Jun; Che, Siyi; Liu, Jiao; Long, Xiaoru (Frontiers in Immunology, 2025)
Glucocorticoid resistance is a challenging problem in clinical practice. Increasing glucocorticoid sensitivity and reducing resistance are important in the management of certain diseases. In steroid-resistant airway inflammatory diseases, glucocorticoid receptor (GR) expression is reduced, and impaired GR nuclear translocation is closely related to glucocorticoid resistance. Histone deacetylase SIRT1 regulates steroid hormone receptor activity and interacts with the androgen receptor and GR. In some glucocorticoid-resistant diseases, SIRT1 expression is reduced. Here, we review recent advances in the role of SIRT1 in regulating glucocorticoid signaling. First, we describe the structure, tissue expression, and subcellular localization of SIRT1. We also discuss the molecular mechanisms by which SIRT1 regulates glucocorticoid activity and its association with GR, as well as the mechanisms and roles of SIRT1 in several common glucocorticoid-resistant diseases. SIRT1 may serve as a potential therapeutic target, providing an opportunity for the treatment of glucocorticoid-resistant diseases.